Biochemical Characterization of an Arginine 2, 3‐Aminomutase with Dual Substrate Specificity. Issue 9 (25th May 2020) - Zhao, Junfeng; Ji, Wenjuan; Ji, Xinjian; Zhang, Qi
Summary of main observation and conclusion: The radical S‐adenosylmethionine (SAM) aminomutases represent an important pathway for the biosynthesis of β‐amino acids. In this study, we report biochemical characterization of BlsG involved in blasticidin S biosynthesis as a radical SAM arginine 2, 3‐aminomutase. We showed that BlsG acts on both L ‐arginine and L ‐lysine with comparable catalytic efficiencies. Similar dual substrate specificity was also observed for the lysine 2, 3‐aminomutase from Escherichia coli (LAMEC ). The catalytic efficiency of LAMEC is similar to that of BlsG, but is significantly lower than that of the enzyme from Clostridium subterminale (LAMCS ), which acts only on L ‐lysine rather than on L ‐arginine. Moreover, we showed that enzymes can be grouped into two major phylogenetic clades, each corresponding to a certain C3 stereochemistry of the β‐amino acid product. Our study expands the radical SAM aminomutase members and provides insights into enzyme evolution, supporting a trade‐off between substrate promiscuity and catalytic efficiency. Abstract :